خدمات الارشاد الأکادیمى عن بعد لطلاب الدراسات العلیا بقسم المکتبات والمعلومات بجامعة حلوان - د. لمیاء مختار عبد الحمید (المجلة الدولية لعلوم المكتبات والمعلومات)
The increased political, social and economic demands in the last fewyear, along with the modern technological development, have led to theoccurrence of changes in education provision systems and the ways of reachingstudents. Therefore, there emerged the opportunity to provide a more specializedsupport to students through the provision of remote academic guidance.The application of using academic guidance services through electronicdevices, whether computers or smartphones, for postgraduate students within thedepartments of libraries and information is also considered an important link inthe series of technological development witnessed by our current era.In order to provide academic guidance services at any time and fromanywhere using these modern technological tools, the academic remoteguidance aims through these modern technological tools to provide guidanceservices for postgraduate students in the departments of libraries and informationin Egyptian universities, in order to develop their personalities academically, anddevelop their skills in various areas in accordance with the international qualitystandards, as academic guidance is considered an essential element of theuniversity student's experience.Providing academic counseling is also considered one of the institutionalfunctions that links all students to the institution, i.e. one that develops in them asense of belonging. Coinciding with the increase in the complexity of theeducational curricula and the expansion of the educational options, the pressureto make that academic experience a meaningful experience that can be appliedto students wherever they may be, has also increased. For this purpose, the study aims to fulfill a set of objectives; namely:introducing the role of using computers in supporting academic guidance,introducing the role of smartphone applications in supporting academic guidance,introducing the requirements of the department of libraries and information atHelwan University for using such modern technological tools, identifyingproblems that the departments of libraries and information may face when usingthis new service and identifying the technical and professional requirements thatthe departments of libraries and information need for that technological change